2019
DOI: 10.1021/acsaelm.9b00107
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable and Radiation Hard Ferroelectric Hf0.5Zr0.5O2 Thin Films on Muscovite Mica for Flexible Nonvolatile Memory Applications

Abstract: Metal–ferroelectric–metal (MFM) capacitors on flexible substrates are promising for flexible nonvolatile memory applications, while the insufficient scalability of perovskite-based ferroelectric thin films and the difficulty of direct integration of high performance ferroelectric thin films on current conventional flexible substrates are the most serious obstacles to their practical applications. Meanwhile, performance under harsh conditions (such as high temperature and high total ionized dose (TID) radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…The integrated peak intensity of the o(111)/t(101) reflection as a function of temperature (Figure 2f) shows a gradual decrease with temperature and the absence of phase transition. For HfO 2 , Hf 0.5 Zr 0.5 O 2 , and ZrO 2 films, polarization dependence on temperature shows a small decrease with temperature with the absence of phase transition in the explored temperature range (Supporting Information, Figure S9) in agreement with the reported results in polycrystalline 39 and epitaxial 40 films. Thus, only the HfO 2 film undergoes a phase transition to the high temperature stable monoclinic phase.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…The integrated peak intensity of the o(111)/t(101) reflection as a function of temperature (Figure 2f) shows a gradual decrease with temperature and the absence of phase transition. For HfO 2 , Hf 0.5 Zr 0.5 O 2 , and ZrO 2 films, polarization dependence on temperature shows a small decrease with temperature with the absence of phase transition in the explored temperature range (Supporting Information, Figure S9) in agreement with the reported results in polycrystalline 39 and epitaxial 40 films. Thus, only the HfO 2 film undergoes a phase transition to the high temperature stable monoclinic phase.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…[41] Previous studies showed that HZO thin films directly grown on flexible mica substrates had robust ferroelectricity and promising application potential in flexible electronics. [42][43][44][45] The distinct advantage of our freestanding HZO membranes is that they can be easily transferred to almost any substrate to fabricate electronic devices, including substrates that cannot be annealed at high temperatures. Here we transferred the HZO capacitors onto mica as an example to demonstrate the robust ferroelectricity of our freestanding HZO membranes in flexible electronic devices.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are observations of large polarizations that are comparable with those of perovskite‐oxide ferroelectrics, doped HfO 2 thin films suffer from severe fatigue problems during bipolar electric field cycling. [ 21–30 ] Switchable polarizations ( P SW ) have been observed to be degraded to zero after ≈10 9 cycles in Hf 0.5 Zr 0.5 O 2 and Y:HfO 2 thin films. [ 22,28 ] In addition, dramatically increased leakage currents and dielectric breakdown appeared in fatigued HfO 2 thin films.…”
Section: Figurementioning
confidence: 99%